2022
DOI: 10.3390/biomedicines10020402
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Phenotypic Transformation in Heart Failure Caused by Coronary Heart Disease and Dilated Cardiomyopathy: Delineating at Single-Cell Level

Abstract: Heart failure (HF) is known as the final manifestation of cardiovascular diseases. Although cellular heterogeneity of the heart is well understood, the phenotypic transformation of cardiac cells in progress of HF remains obscure. This study aimed to analyze phenotypic transformation of cardiac cells in HF through human single-cell RNA transcriptome profile. Here, phenotypic transformation of cardiomyocytes (CMs), endothelial cells (ECs), and fibroblasts was identified by data analysis and animal experiments. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…2.1 | Single-cell RNA sequencing (scRNA-seq) analysis scRNA-seq data from heart tissues of TAC-model mice was obtained from the Gene Expression Omnibus (GEO) database (GSE120064), and was analyzed with R package Seurat as previously described. 19,23…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2.1 | Single-cell RNA sequencing (scRNA-seq) analysis scRNA-seq data from heart tissues of TAC-model mice was obtained from the Gene Expression Omnibus (GEO) database (GSE120064), and was analyzed with R package Seurat as previously described. 19,23…”
Section: Methodsmentioning
confidence: 99%
“…Heart‐resident macrophages are activated into pro‐inflammatory M1 type to trigger inflammatory response, resulting in accelerated deterioration of cardiac function in HF 11,12,17 . Cardiac fibroblasts are activated to trigger myocardial fibrosis in HF 18,19 . Single‐cell RNA sequencing of pressure overload‐induced pathological cardiac hypertrophy in mice showed that macrophage activation and subtype switching, a key event at middle‐stage of cardiac hypertrophy 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it can result in diminished cardiac compliance, necrosis of cardiomyocytes, and cardiac remodeling, ultimately leading to impaired myocardial contractility and cardiac dysfunction. These pathological changes serve as crucial links between hypertension, coronary heart disease, diabetes, and the development of heart failure (10)(11)(12). Cardiac fibroblasts represent the predominant population of mesenchymal cells within the cardiac tissue.…”
Section: Current Status Of Treatment For Cardiac Fibrosismentioning
confidence: 99%